Jobs, Growth, and Governance in the Middle East and North Africa : Unlocking the Potential for Prosperity - World Bank (World Bank, Washington, DC, 2016)
This report identifies the following as the fundamental challenges and changes that the Middle East and Africa must meet and make in order to improve living standards over the next two decades: Between eighty and one hundred million new jobs to be created by 2020. Economic growth to be lifted from a sluggish 3.4 percent over the late 1990s to at least 6-7 percent a year. Governance to move from traditional autocracies to more inclusive governments, accountable to the people. Women to be more equitably included in economic activity and to harness the significant potential economic benefits from an increasingly educated and healthy female population. Public sectors to open the door to more private initiative. Economies dependent on oil and workers' remittances to diversify into manufacturing and services. Closed trading regimes to integrate with new trading partners in the region and the world. Impossible? No. Imperative? Yes. The political imperatives for such change and the stability of the old order are two opposing forces. The balance is shifting toward the need for reform as joblessness and slow growth make the old order increasingly costly and unsustainable.